'Crops for the State!' Agriculture and the Countryside in 1950s Propaganda Posters of Central and Eastern Europe. (May 2014) - N, U; I, H
Abstract : The paper discusses an international exhibition of propaganda posters from the 1950s showing agriculture in the light of socialist propaganda. The aim and the major value of the exhibition was to showcase the similarity of propaganda posters in many countries of Central and Eastern Europe, while simultaneously exploring each country's specificities. The posters show propaganda view of 'progressive' socialist agriculture, whereas the reality was quite different. It is interesting to see how propaganda posters reflected all elements of 'successful' socialist agriculture: collective farms, mandatory supplies, agriculture plans, an alliance of workers and peasants, work leadership, People's authorities, elections, friendship with the USSR, mechanization of agriculture and electrification of rural areas, prosperity and peace, harvest festivals, fighting the Colorado beetle, fighting the kulak, and others. The exhibition organizers were also keen to observe and make comments on reactions of museum visitors to a display on such a controversial topic.